ANALISA KURIKULUM NASIONAL MATA PELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) TINGKAT SEKOLAH DASAR (SD) DALAM MENGEMBANGKAN ISLAM YANG MODERAT (RAHMATAN LIL ALAMIN) - Solihin, Nandang; Adil, Ustad (LP2M Universitas PTIQ Jakarta, 2023)
The recent rise of radicalism and terrorism must be anticipated early on. Islam is a religion of peace, respect for differences (tawasuth), teaches tolerance (tasamuh). This study uses a literature method that systematically collects books related to research and analyzes the national curriculum for Islamic Religious Education at the elementary school level in developing moderate Islam. The results of this study are the national curriculum for Islamic Religious Education subjects at the Elementary School level in developing moderate Islam for students which contains the importance of increasing faith, the importance of praying, morals or ethics, sharing, good friends, brotherhood, tolerance, and materials that directing their students to do good. While the tools needed are learning methods that are appropriate and easily understood by students, including lecture methods, discussions, assignments and training methods as well as the qualifications of undergraduate teachers. Meanwhile, the recent rise of radicalism and terrorism is due to environmental influences, places to hang out, accessible media, friendship factors, and so on